Effects of Urbanization on the Temperature Inversion Breakup in a Mountain Valley with Implications for Air Quality - Rendón, Angela M.; Salazar, Juan F.; Palacio, Carlos A.; Wirth, Volkmar; Brötz, Björn (Journal of applied meteorology and climatology, 2014)
Many cities located in valleys with limited ventilation experience serious air pollution problems. The ventilation of an urban valley can be limited not only by orographic barriers, but also by urban heat island–induced circulations and/or the capping effect of temperature inversions. Furthermore, land-use/-cover changes caused by urbanization alter the dynamics of temperature inversions and urban heat islands, thereby affecting air quality in an urban valley. By means of idealized numerical simulations, it is shown that in a mountain valley subject to temperature inversions urbanization can have an important influence on air quality through effects on the inversion breakup. Depending on the urban area fraction in the simulations, the breakup time changes, the cross-valley wind system can evolve from a confined to an open system during the daytime, the slope winds can be reversed by the interplay between the urban heat island and the temperature inversion, and the breakup pattern can migrate from one dominated by the growth of the convective boundary layer to one also involving the removal of mass from the valley floor by the upslope winds. The analysis suggests that the influence of urbanization on the air quality of an urban valley may lead to contrasting and possibly counterintuitive effects when considering temperature inversions. More urban land does not necessarily imply worse air quality, even when considering that the amount of pollutants emitted grows with increased urbanization.